FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEBERADAAN BAHAN BERBAHAYA BISPHENOL A (BPA) YANG TERKANDUNG DALAM KONTAINER PLASTIK MAKANAN DAN MINUMAN - I Nyoman Gede Suyasa (Poltekkes Kemenkes Denpasar, 2018)
Abstract. The use of plastics as food packaging are inherent to the life of the community. The main ingredient is the manufacture of polycarbonate plastics compound bisphenol A (BPA). BPA may get into the human body is mainly because of its ability to migrate into foodstuffs were packed. BPA has the potential to lead to abnormal development of the endometrium which can cause infertility and increase the risk of developing breast cancer. The aim of research to determine the relationship of knowledge, ready and action by the presence of plastic containers. An observational study with design cross setctional, a large sample of the population housewife in Badung with 360 housewives. Sampling methods of sampling area. The technique of collecting primary data on the characteristics, knowledge, attitude and practice using a questionnaire by the officer. Analysis of data using statistical multivarianceThe results were obtained knowledge is not good as much as 307 respondents (85.28%), good attitude of 358 respondents (99.44%), the action is not good as much as 258 respondents (71.67%) and the presence in the household plastic containers of 328 ( 91.11%). No relation between knowledge and action by the presence of a plastic container with a P - 0.000, variable attitudes are not related to the presence of a plastic container with a value of P = 1.000. The dominant variable related to the presence of plastic containers is an action expB value = 5.975. Expected housewives use plastic containers as food and beverage containers in accordance with the code designationKeywords:Bisphenol A, Plastics, Food and Beverages